Establishment and evaluation of chronic obstructive pulmonary disease model by chronic exposure to motor vehicle exhaust combined with lipopolysaccharide instillation. Issue 11 (4th September 2018) - Shu, Jiaze; Lu, Wenju; Yang, Kai; Zheng, Qiuyu; Li, Defu; Li, Yi; Kuang, Meidan; Liu, Hanwei; Li, Ziying; Chen, Yuqin; Zhang, Chenting; Luo, Xiaoyun; et al.
Abstract : New Findings: What is the central question of this study? In this study, by using motor vehicle exhaust (MVE) exposure with or without lipopolysaccharide (LPS) instillation, we established, evaluated and compared MVE, LPS and MVE+LPS treatment‐induced chronic obstructive pulmonary disease (COPD) models in mice. What is the main finding and its importance? Our study demonstrated that the combination of chronic exposure to MVE with early LPS instillation can establish a mouse model with some features of COPD, which will allow researchers to investigate the underlying molecular mechanisms linking air pollution and COPD pathogenesis. Abstract: Although it is well established that motor vehicle exhaust (MVE) has a close association with the occurrence and exacerbation of chronic obstructive pulmonary disease (COPD), very little is known about the combined effects of MVE and intermittent or chronic subclinical inflammation on COPD pathogenesis. Therefore, given the crucial role of inflammation in the development of COPD, we wanted to establish an animal model of COPD using both MVE exposure and airway inflammation, which could mimic the clinical pathological changes observed in COPD patients and greatly benefit the study of the molecular mechanisms of COPD. In the present study, we report that mice undergoing chronic exposure to MVE and intratracheal instillation of lipopolysaccharide (LPS) successfully established COPD, as characterized by persistent air flow limitation, airway inflammation, inflammatory cytokine production, emphysema and small airway remodelling. Moreover, the mice showed significant changes in ventricular and vascular pathology, including an increase in right ventricular pressure, right ventricular hypertrophy and remodelling of pulmonary arterial walls. We have thus established a new mouse COPD model by combining chronic MVE exposure with early intratracheal instillation of LPS, which will allow us to study the relationship between air pollution and the development of COPD and to investigate the underlying molecular mechanisms. Abstract :